Clinical characteristics of patients with CRSwNP with intensely high eosinophil level - Ling Ma; Jianbo Shi; Kanghua Wang; Yueqi Sun; Rui Xu (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Background High tissue and blood eosinophils are linked to poor treatment outcome in patients with chronic rhinosinusitis with nasal polyps (CRSwNP). However, the difference between the patients with different level of blood or tissue eosinophilia in relation to disease control is still lacking. Objectives This study aimed to characterize patients with CRSwNP with intensely high eosinophil level. Methods A retrospective study of CRSwNP patients underwent endoscopic sinus surgery was conducted. The patients were subdivided with various cut‐off values of blood and tissue eosinophils. Tissue eosinophils of ≥50% and 10%–20% were defined as intensely high tissue eosinophils (IH‐tissue‐eos) and high tissue eosinophils (H‐tissue‐eos), respectively. Blood eosinophils of ≥0.6 × 109/L and 0.2 × 109/L–0.3 × 109/L were defined as intensely high blood eosinophils (IH‐blood‐eos) and high blood eosinophils (H‐blood‐eos). Clinical characteristics, Lund‐Mackay score (LMS), and disease control status were compared between subgroups. Results A total of 302 patients were enrolled. There was a trend toward a higher rate of uncontrolled disease when the patients subdivided by blood eosinophil cut‐off values ranged from 0.1 × 109/L to 0.6 × 109/L. The controlled patients accounted for 27%, 36%, 22%, and 31%, and the uncontrolled patients 46%, 32%, 52%, and 31% of patients in IH‐tissue‐eos, H‐tissue‐eos, IH‐blood‐eos, and H‐blood‐eos subgroup, respectively. The percentages of patients in the three categories of control were not significantly different between IH‐tissue‐eos and H‐tissue‐eos subgroups. By contrast, the IH‐blood‐eos subgroup had higher percentages of current smoker and asthma, preoperative LMS and tissue eosinophil percentage, and showed a trend toward a higher rate of uncontrolled subjects compare with the H‐blood‐eos subgroup. Conclusion CRSwNP patients with IH‐blood‐eos (≥0.6 × 109/L) may be possibly associated with a poorer disease control than those with levels near the threshold of blood eosinophilia (0.2 × 109/L–0.3 × 109/L). Further larger, preferably prospective studies are needed to confirm this relationship. Level of Evidence: 4.